1975
DOI: 10.1149/1.2134441
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nitride Films by Direct RF Sputter Deposition

Abstract: 1271 not N2, as the carrier gas. (iii) The deposition rate increases initially with XPH3 at all temperatures studied. A maximum rate at XPH3 ~ 0.8 is observed in the Ar system, but not the N2 system. (iv) Deposition of high P~O5 content films, i.e., at XpH3 > 0.5, appears to be inhibited by the presence of N2. AcknowledgmentThe authors would like to thank P. Sargent for technical assistance and M. McConnell for performing the microprobe analysis.Publication costs of this article were partially assisted by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…They are characterized by activation energies which lie within the forbidden bandgap of the semiconductor, and by their thermal capture and emission rates for minority and majority carriers, respectively. Their contribution toward diode leakage is governed by the Shockley-Read-HaI1 generation-recombination theory (1). The most effective centers, in terms of the generation component, lie near the midgap of the semiconductor.…”
Section: Precipitation-induced Currents and Generation-recombination ...mentioning
confidence: 99%
“…They are characterized by activation energies which lie within the forbidden bandgap of the semiconductor, and by their thermal capture and emission rates for minority and majority carriers, respectively. Their contribution toward diode leakage is governed by the Shockley-Read-HaI1 generation-recombination theory (1). The most effective centers, in terms of the generation component, lie near the midgap of the semiconductor.…”
Section: Precipitation-induced Currents and Generation-recombination ...mentioning
confidence: 99%
“…Silicon nitride may be deficient in nitrogen and silicon dioxide deficient in oxygen. The addition of nitrogen during nitride sputtering or oxygen during oxide sputtering improves the stoichiometry of the fIlm [242,243]. Another method is to sputter, e.g., silicon with oxygen or nitrogen, or titanium with oxygen, rather than with argon, to form silicon dioxide, silicon nitride, or titanium oxide.…”
Section: Reactive Sputter Depositionmentioning
confidence: 99%
“…Studies of gold doping in Si, for example, have shown atomic gold to pile up in n + regions (9,10). A second approach (11,12) has been to study the unintentional loss of desired lifetimecontrolling impurity species during subsequent device processing steps or by aging processes at operating temperatures or higher (13,14).…”
Section: Department Of Electrical Engineering Carnegie-mellon Univermentioning
confidence: 99%
“…Studies of gold doping in Si, for example, have shown atomic gold to pile up in n + regions (9,10). A second approach (11,12) has been to study the unintentional loss of desired lifetimecontrolling impurity species during subsequent device processing steps or by aging processes at operating temperatures or higher (13,14). Using neutron activation analysis, platinum has been studied here for its resistance to unintentional gettering by processing cycles accompanying its introduction into the silicon lattice.…”
Section: A Comparison Of the Process-inducedmentioning
confidence: 99%